Revitalization of islamic education at the imam hatip school in turkey - Bibi Suprianto (IAIN Salatiga, 2020)
This research tells about the revitalization of Islamic education at the Imam Hatip school during Erdogan’s leadership. Also, this study reveals the beginning of Islamic education in Turkey during the Ottoman Empire, the Attaturk government, and continued by Erdogan’s leadership. This research aims to find out about Islamic education during Erdogan’s reign, such as the Imam Hatip Islamic schools, which are the focus of modern Islamic education by the Turkish community. Besides, the research objective is to prove Islamic schools in Turkey developed the contemporary curriculum. The method used is library research, which focuses on journals and books as primary data. The results and implications of the study are in the form of texts that provide strong research arguments about modern Islamic education that is currently developing in the world